RESEARCH ON MECHANISM OF SHENLING BAIZHU SAN ON DIABETIC OBESITY BASED ON META-ANALYSIS AND NETWORK PHARMACOLOGY - ZHOU, XIAOLING; TANG, LIPING; WU, DIYAO; ZHANG, XINYOU (International Journal of Applied Pharmaceutics, 2024)
Objective: To evaluate the therapeutic effects of Shenling Baizhu San on diabetic obesity by literature meta-analysis and analyze the mechanism of Shenling Baizhu San on diabetic obesity by combining network pharmacology and animal experiment methods. Methods: 1. Relevant literatures at home and abroad were included. The BMI, glycosylated hemoglobin (HbA1c), 2h postprandial blood glucose (2hPG), Fasting Blood Glucose (FBG), Homa-IR, waist-to-hip ratio were used as outcome indicators to evaluate the effects of Shenling Baizhu San on diabetic obesity. 2. The related genes of diabetes obesity in GEO chip were downloaded, and the targets of Shenling Baizhu San were downloaded in TCMSP, TCMID and BATMAN-TCM. Protein interaction analysis was carried out on the intersection targets of the two, and then the core target protein was screened out based on topological analysis. 3. The model of diabetic obese mice was established, and the mice were treated with Shenling Baizhu San after grouping. After two weeks, the body mass, blood sugar and Lee's index of mice in each group were measured. The volume changes of adipocytes in each group were analyzed by Hematoxylin-Eosin method, and the concentrations of cholesterol, triglyceride and core target protein in mice serum were measured. Results: 1. A total of 9 literatures were included, the data were complete, no publication bias was found, and the evaluation was low risk. After administration of Shenling Baizhu San, the BMI, HbA1c, 2hPG, FBG, Homa-IR and waist-hip ratio of the patients were significantly improved. 2. There were 337 genes related to diabetes obesity, 2067 targets of Shenling Baizhu San and 59 intersecting targets. There were 7 signal pathways related to the effect of Shenling Baizhu San on diabetes obesity, including Biosynthesis of unsaved fatty acids, Fatty acid metabolism and so on. 3. The results of animal experiment showed that the blood glucose of mice treated with Shenling Baizhu San was not significantly changed, the body weight and Lee's index showed a significant downward trend, the fat cells were significantly reduced, and the contents of cholesterol and triglyceride, the concentration of APO-E, IGF-1 and PAI-1 protein showed a downward trend. Conclusion: Based on the results of meta-analysis and animal experiments, Shenling Baizhu San had obvious therapeutic effect on diabetic obesity, and its mechanism may be related to influencing the synthesis of unsaturated fatty acids and fatty acids, reducing the transformation of glucose and fat, correcting the imbalance of energy metabolism in the body, and promoting the decomposition of adipose tissue by up-regulating autophagy.